2016
DOI: 10.1155/2016/5785819
|View full text |Cite|
|
Sign up to set email alerts
|

Fish Collagen Promotes the Expression of Genes Related to Osteoblastic Activity

Abstract: Tilapia type I atelocollagen (TAC) is a strong candidate for clinical application as its biological scaffold due to a high degeneration temperature and biologically safe properties. The aim of this study was to confirm the biological effects of TAC in vitro on osteoblastic cells, simulating its clinical application. The proliferation and differentiation of typical preosteoblasts, MC3T3-E1 cells, were investigated using a microarray analysis, staining assay for mineralization, and real-time PCR analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Furthermore, collagen's ability to regenerate bone has been shown to be successful in rat models of menopausal osteoporosis [49]. Marine collagen is able to increase bone mineral density and osteoblastic activity, serving protective effects against bone degeneration [49][50][51][52][53]. Collagen has also been shown to induce chondrogenic differentiation and prevent the development of osteoarthritis (OA) [54,55].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, collagen's ability to regenerate bone has been shown to be successful in rat models of menopausal osteoporosis [49]. Marine collagen is able to increase bone mineral density and osteoblastic activity, serving protective effects against bone degeneration [49][50][51][52][53]. Collagen has also been shown to induce chondrogenic differentiation and prevent the development of osteoarthritis (OA) [54,55].…”
Section: Introductionmentioning
confidence: 99%
“…Bone regeneration need osteoprogenitor cells, signaling molecules, and scaffolds to trigger and regulate osteogenic differentiation so that new bone is eventually formed 2,24,25 . Collagen derived from mammals has been used as a biomass scaffold and various studies have shown that collagen can induce osteoblast cell proliferation 26,27,28 .…”
Section: Resultsmentioning
confidence: 99%
“…In the article titled "Fish Collagen Promotes the Expression of Genes Related to Osteoblastic Activity" [1], there were errors, which should be corrected as follows:…”
mentioning
confidence: 99%